Evolution of public healthcare facilities designs to health trend in Malaysia : a retrospect of nation building from pre colonial to today - Mohd Nawawi, Norwina (2012)

(untitled)
Malaysia has its own inbuilt history of evolution of healthcare facilities designs from the traditional to contemporary mega structures we witness today. Each designs has its own story foretold the epidemiology phenomena, capacity and inspiration of a developing nation. From simplistic idea of housing aspects of health in single isolated buildings to complex structures that needs reviewing towards a sustainable future. The pictorial presentations briefly explore Malaysian public healthcare facilities from its humble beginnings in nation building from pre-colonial to what it is today. The objective is to provide ideas on the basis of why and how these designs were pragmatically evolved through time, to professionals, allied disciplines and users. Both qualitative and quantitative methodologies were adopted for this continuing research. Primary and secondary data, through literature review, observations, random interviews, post occupancy evaluations and hands-on experiences, were utilised. The significance of this presentation includes a sense of importance to the role of individual players in the healthcare services, construction and industry, the trust that our Creator, and humanity had conferred on us, towards contributing and sustaining a healthy and hence a ‘wealthy” nation.